PENERAPAN MEDIA ARTICULATE STORYLINE 3 SEBAGAI PEMBELAJARAN INTERAKTIF PADA MATERI SISTEM PEREDARAN DARAH - Amir, Daniah; Lubis, Silvi Puspa Widya (Jurnal Dedikasi Pendidikan, 2025)
This research aims to develop and examine the feasibility of learning media based on Articulate Storyline 3 for circulatory system material for grade XI students at MAN 1 Pidie Jaya. The media development utilized a modified ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. This study employed both quantitative and qualitative approaches, involving subject matter experts, media experts, and students as respondents. Validation by subject matter and media experts was conducted to assess media feasibility, while small group trials were performed to determine student responses. The results indicate that the developed learning media has a high validity level, with an average assessment of 86% from subject matter experts and 87.67% from media experts. Student response to the learning media was also highly positive, with an acceptance rate of 89%. The media's strengths include interactive displays, animations that facilitate understanding, and interactive quiz features. However, there are some limitations such as computer device requirements and potential technical constraints. Overall, the developed Articulate Storyline 3 learning media has proven to be valid, practical, and effective for use in learning circulatory system material at the high school level